A primer on investigating the after effects of acute bouts of physical activity on cognition. (January 2019) - Pontifex, Matthew B.; McGowan, Amanda L.; Chandler, Madison C.; Gwizdala, Kathryn L.; Parks, Andrew C.; Fenn, Kimberly; Kamijo, Keita
Abstract: An emerging body of evidence has begun to document the beneficial after effects of single bouts — or doses — of physical activity for cognition. This article highlights a selection of common themes and critical delimitations that investigators new to this area of research as well as those currently working in the field may find relevant for advancing research in this area. The intent of this article is to provide a stimulus for future investigations to enhance not only the breadth and depth of the evidence, but also the experimental rigor. In doing so, a number of fundamental considerations are discussed including the aspects of cognition predominantly focused upon to date, issues related to the dose of the physical activity (i.e., how long the after effects persist, what characteristics of the dose may maximize the cognitive after effects), potential moderating variables, as well as potential underlying mechanisms. Additionally, discussion is provided regarding methodological considerations for future investigations including implications of the experimental design, control conditions, and cognitive assessment utilized, as well as statistical and reporting considerations to facilitate transparency. By calling attention to these areas, the hope is that future research may advance our understanding of the underlying mechanisms, theoretical development, and clinical relevance of the cognitive after effects of these single doses of physical activity. Highlights: Cognition is enhanced following single bouts of physical activity. This review highlights common themes and critical delimitations in this area. Considerations for future investigations are discussed.